Carboxylic acids accelerate acidic environment-mediated nanoceria dissolution. Issue 4 (21st April 2019) - Yokel, Robert A.; Hancock, Matthew L.; Grulke, Eric A.; Unrine, Jason M.; Dozier, Alan K.; Graham, Uschi M.
Abstract: Ligands that accelerate nanoceria dissolution may greatly affect its fate and effects. This project assessed the carboxylic acid contribution to nanoceria dissolution in aqueous, acidic environments. Nanoceria has commercial and potential therapeutic and energy storage applications. It biotransforms in vivo . Citric acid stabilizes nanoceria during synthesis and in aqueous dispersions. In this study, citrate-stabilized nanoceria dispersions (∼4 nm average primary particle size) were loaded into dialysis cassettes whose membranes passed cerium salts but not nanoceria particles. The cassettes were immersed in iso-osmotic baths containing carboxylic acids at pH 4.5 and 37 °C, or other select agents. Cerium atom material balances were conducted for the cassette and bath by sampling of each chamber and cerium quantitation by ICP-MS. Samples were collected from the cassette for high-resolution transmission electron microscopy observation of nanoceria size. In carboxylic acid solutions, nanoceria dissolution increased bath cerium concentration to >96% of the cerium introduced as nanoceria into the cassette and decreased nanoceria primary particle size in the cassette. In solutions of citric, malic, and lactic acids and the ammonium ion ∼15 nm, ceria agglomerates persisted. In solutions of other carboxylic acids, some select nanoceria agglomerates grew to ∼1 micron. In carboxylic acid solutions, dissolution half-lives were 800–4000 h; in water and horseradish peroxidase they were ≥55, 000 h. Extending these findings to in vivo and environmental systems, one expects acidic environments containing carboxylic acids to degrade nanoceria by dissolution; two examples would be phagolysosomes and in the plant rhizosphere.